PENGARUH MEDIA LOOSEPART DALAM KURIKULUM MERDEKA BELAJAR PADA ANAK USIA DINI DI RA ANANDA SURABAYA - Norma Diana Fitri; Indaria Tri Hariyani; Noviardani Kartika Prameswari; Mirapradipta Aryanti; Alfina Citrasukmawati (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2023)
The fundamental problem in this study is the low ability of children to solve a problem at RA Ananda Surabaya. Before children receive loose part learning at RA Ananda Surabaya, early childhood abilities have not been said to be successful in identifying problems and finding solutions according to their creative ideas. Therefore, researchers apply the loose part learning method at RA Ananda Surabaya so that teachers can plan lessons based on developing higher order thinking skills in children, Higher Order Thinking Skills (HOTS) in the independent learning curriculum.This study aims to understand how to apply loose part-based learning to RA Ananda Surabaya children who are still early in implementing the independent learning curriculum to solve a problem with creative ideas. This research includes quantitative description research, its implementation is carried out for 1 week, namely through observation in class learning. In this study the subjects observed were RA Ananda Surabaya children in group A, totaling 9 of them 5 boys and 4 girls. The ability to solve problems in this observation include: (a). children can think critically to solve problems in everyday life (b). arouse curiosity and find a solution to a problem. Data collection techniques are carried out through: (1) observation; (2) interviews; and (3) documentation. Data processing was carried out using percentage techniques and t-test (praired sample t-test). Based on the results of the t test calculation data, the value of tcount ? ttable (7.466 > 1.76131) is obtained. So it can be concluded that H0 is rejected and H1 is accepted, which means that there is an influence of loose parts media on children's ability to solve problems in the independent learning curriculum implemented by group A RA Ananda Surabaya, thus it can be concluded that there is a significant influence on children's ability to solve problems by using loose part learning in the independent learning curriculum.